Building Morocco's Resilience : Inputs for an Integrated Risk Management Strategy - World Bank (Washington, DC, 2014)
Top decision makers and governments worldwide are witnessing an accelerating number of major shocks-global financial crises, hyper-volatility in commodity prices, devastating natural disasters, intercontinental pandemics as well as the changing nature of terrorism threats. These shocks, which inflict human suffering and major social, economic and political disruption, are fundamentally changing how governments view the importance of good risk management and the need to strengthen national resilience. As a consequence, risk management has evolved from being a technical issue to a strategic consideration. This report is input for the government of Morocco's development of an integrated risk management strategy. Developing and adopting a national strategy for integrated risk management (IRM) will make Morocco not only better prepared to avoid future crises, and more reactive and resilient if and when they occur, but also helps the government make more informed decisions on resource allocation and prioritization.